A new multi-field coupled dynamic analysis method for fracturing pipes - Yao, Liming (2022)
In petrochemical, marine, and other fields, high-concentration solid-liquid two-phase flow induced pipe vibration has always been a problem worthy of attention. Especially when the oil pipe transports solid-liquid two-phase flow, researchers have introduced the equivalent density of the two-phase flow into the fluid momentum equation to consider the influence of the two-phase flow on pipes with vibrations. This method ignores the influence of particle collision and accumulation in the pipe on fluid flow and pipe vibration, which makes it impossible to fully predict the dynamic state of the pipes. Therefore, this paper presents the fluid-particle-pipe multi-field coupling analysis method (CFD-DEM-FEM method) for the first time to analyze the pipe vibration induced by the two-phase flow. The analysis found that when the velocity of the two-phase flow and the sand ratio increase, at the same time the diameter ratio decreases, the more significant the collision and accumulation of particles at the location where the pipe diameter changes, as well as the vibration amplitude of the pipe are all getting bigger. In addition, high fluid velocity can produce high-amplitude and high-frequency vibrations, while high sand ratio can produce low-amplitude high-frequency vibrations. For the pipe vibration amplitude and frequency values, the relative errors between the current computational results and those from experiments are less than 15%, indicating that our multi-field coupling calculation method can be used in the pipe vibration induced by solid-liquid two-phase flow. Our research results can be used to guide the structural design and process design of high-concentration solid-liquid two-phase flow pipe, and reduce the chance of two-phase flow-induced pipe vibration damage.